2011
DOI: 10.1074/jbc.m111.235465
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Covalent Heterogeneity Reveals Simple Folding Behavior for P4-P6 RNA

Abstract: RNA folding landscapes have been described alternately as simple and as complex. The limited diversity of RNA residues and the ability of RNA to form stable secondary structures prior to adoption of a tertiary structure would appear to simplify folding relative to proteins. Nevertheless, there is considerable evidence for long-lived misfolded RNA states, and these observations have suggested rugged energy landscapes. Recently, single molecule fluorescence resonance energy transfer (smFRET) studies have exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 57 publications
9
48
0
Order By: Relevance
“…This ability, along with homogenous molecular behavior (ref. 90 and Materials and Methods), allows construction of a folding framework under uniform conditions, avoiding uncertainties and complications from extrapolation of RNA behavior across conditions (62,82,91). Example traces and data quality analyses for all constructs can be found in Dataset S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This ability, along with homogenous molecular behavior (ref. 90 and Materials and Methods), allows construction of a folding framework under uniform conditions, avoiding uncertainties and complications from extrapolation of RNA behavior across conditions (62,82,91). Example traces and data quality analyses for all constructs can be found in Dataset S1.…”
Section: Resultsmentioning
confidence: 99%
“…1C) (60). Also, prior P4-P6 smFRET work revealed molecular heterogeneity from covalent damage caused by standard RNA treatments and showed that this damage could be avoided to yield highly homogeneous populations (90).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2C). These resonances are therefore unlikely to arise from UV chemical damage to the RNA (Greenfeld et al 2011;Kladwang et al 2012) or from N + 1 products during in vitro RNA transcription (Milligan et al 1987;Cazenave and Uhlenbeck 1994;Pleiss et al 1998;Helm et al 1999). Rather, these additional resonances could reflect an alternative conformation for adenine residues A25, A27, and A28 near the junction that is in slow exchange with the major state.…”
Section: Impact Of Helix On Ssrna Conformation and Dynamics From Cs Amentioning
confidence: 99%
“…At the same time a three-helix junction (P5abc) within the P4-P6 domain folds at least 25 times more rapidly in isolation than when being a part of the wild-type P4-P6 RNA [51]. The fastest observed rate constants for P4-P6 folding are on the order of 10 s −1 [52], much slower than the formation of basic structures such as RNA hairpins, which form on the microsecond timescale [53,54].…”
Section: Prediction Of Folding Nuclei For Domain P4-p6 From the Tetramentioning
confidence: 99%